FROM FIELD RESIDUE TO BIO-BASED PANELS: INDUSTRIAL HEMP SHIVES IN PARTICLEBOARD AND FIBREBOARD PRODUCTION – A COMPREHENSIVE REVIEW - Savov, Viktor; Ivanov, Georgi (Innovation in Woodworking Industry and Engineering design, 2025)
Industrial hemp cultivation generates large quantities of stems and shives (hurd) that remain underutilised despite their attractive characteristics as a renewable lignocellulosic resource. In recent years, hemp shives have been increasingly explored as a partial or full substitute for wood particles and fibres in particleboards, medium-density fibreboards (MDF) and related panel products. This review synthesises the current state of knowledge on the use of industrial hemp stems and shives in bio-based wood panels, covering raw material properties, pre-treatments, panel manufacturing parameters and resulting performance. Particular attention is given to the influence of particle granulometry, density profile, adhesive type (UF, MF including UF/MF blends, pMDI and emerging bio-based binders) and processing conditions on mechanical properties, dimensional stability, thermal and hygric behaviour. The review compares hempbased and conventional wood-based panels in terms of bending strength, internal bond, screw withdrawal resistance, water absorption and thickness swelling, as well as thermal conductivity and moisture buffering capacity relevant to building applications. Environmental and techno-economic aspects, including resource availability, lightweight design and potential for circular construction, are also briefly discussed. Finally, the paper identifies critical research gaps related to long-term durability, fire performance, interface optimisation between hemp particles and novel binders, upscaling from laboratory to industrial production, and standardisation of testing protocols for hemp-based panels. These gaps are used to outline future research directions and innovation pathways needed to fully valorise industrial hemp stems and shives as a reliable feedstock for next-generation bio-based particleboards and fibreboards.